Edible straw formulation from caragenant and gelatin as a solution in reducing plastic waste. Issue 1 (March 2021) - A'yun, S N; Triastuti, J; Saputra, E
Abstract: This study has been undertaken to determine the effect of bioplastic formulations of carrageenan and gelatin on the manufacture of edible straws with water resistance. The research design used was 2 factorial complete random designs (RAL). Edible straws with 20% gelatin addition formulation have the best water resistance value of 65.18%. Based on these results it shows that there is a correlation between the gelatin added and the temperature used in the use of edible straws. Bioplastic formulations can be used as edible straws with the best formulation of carrageenan 3 grams with the addition of 20% gelatin which can be applied to 4°C cold drinks and is best applied to drinks at 25°C.